Kinerja Keuangan sebagai Dasar Pengambilan Keputusan Investasi di Dhyana Pura Beach Resort Seminyak Kuta Badung - SURYATHI, NW.; PUTRA DARMAWAN, DWI; SUARTANA, W. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
The owners of capital who invest in fixed assets, must pay quite a lot of attention to their decisions that they are going to make, not only in connection with buying a fixed asset but also in the next spending which required by fixed assets. The return of investment by the owners of capital can be predicted with the financial performance by using the analysis of ratio. The aims of this research are to find out and analyze the financial performance profiles of Dhyana Pura Beach Resort Seminyak Kuta Badung and the Department of Food and Beverage Dhyana Pura Beach Resort Seminyak Kuta Badung from 2006 to 2010, the appropriateness of investment decision that has been taking by Dhyana Pura Beach Resort Seminyak Kuta Badung, and also to find out the steps in making investment decision. Analysis methods used in this research is the analysis of qualitative and quantitative data. The investment decision that took by Dhyana Pura Beach Resort Seminyak Kuta Badung to invest was right, it can be seen from the result of calculation of payback period where this investment will return in a quite short time, which is in 1 year, 0.24 months, 7 days. On the other hand, based on the calculation of ne present value this investment gave positive value, which is Rp 342,689,038,985.00, with the assumptions of occupancy rates and index prices in normality. These decisions could be taken because of the financial performance of Dhyana Pura Beach Resort Seminyak Kuta Badung from 2006 to 2010 had a good performance, and also the performance of the Department of Food and Beverage Dhyana Pura Beach Resort Seminyak Kuta Badung from 2006 to 2010 showed that the ability of fulfilment all of the obligations either in a short term or in a long term.
Keywords: Financial Performance, Investment Decision